Germ line transformation and in vivo labeling of nuclei in Diptera: report on Megaselia abdita (Phoridae) and Chironomus riparius (Chironomidae) - Caroti, Francesca; Urbansky, Silvia; Fath, Maike; Lemke, Steffen (Development genes and evolution, 2015)
To understand how and when developmental traits of the fruit fly Drosophila melanogaster originated during the course of insect evolution, similar traits are functionally studied in variably related satellite species. The experimental toolkit available for relevant fly models typically comprises gene expression and loss as well as gain-of-function analyses. Here, we extend the set of available molecular tools to piggyBac-based germ line transformation in two satellite fly models, Megaselia abdita and Chironomus riparius. As proof-of-concept application, we used a Gateway variant of the piggyBac transposon vector pBac{3xP3-eGFPafm} to generate a transgenic line that expresses His2Av-mCherry as fluorescent nuclear reporter ubiquitously in the gastrulating embryo of M. abdita. Our results open two phylogenetically important nodes of the insect order Diptera for advanced developmental evolutionary genetics.